Tissue Regeneration - Abdel hay El-Sayed Kaoud, Hussein (IntechOpen, 2018)
Tissue regeneration is a vast subject, with many different important aspects to consider. Regenerative medicine is a new branch of medicine that tries to change the course of chronic diseases and, in many cases, regenerates the organ systems that fail due to age, disease, damage, or genetic defects. The main purpose of this book is to point out the interest of some important topics of tissue regeneration and the progress in this field as well as the variety of different surgical fields and operations. This book includes 7 sections and 11 chapters that provide an overview of the essentials in tissue regeneration science and their potential applications in surgery. The authors of each chapter have given consolidated information on ground realities and attempted to provide a comprehensive knowledge of tissue engineering and regeneration. This book will be useful to researchers and students of biological and biomedical sciences (medical and veterinarian researchers).